Relationship between attitudes toward aging and health literacy among Taiwanese older men - Ming Hao Liang; Shu Hsin Kuo (Journal of Men's Health)
Background: Men’s health issues often receive less attention in public health discussions than women’s health. This study examines how older men’s demographic characteristics influence their attitudes toward aging and health literacy. Methods: A cross-sectional study assessed 157 older men (mean age = 75.57, SD (Standard Deviation) = 7.10) from Tier-C stations. Participants completed the Health Literacy Questionnaire for Older Adults (HLQ-QA) and the Taiwan Attitude Toward Aging Questionnaire. T-tests compared aging perceptions and health literacy abilities, while regression analyses assessed the influence of attitudes on health literacy. Results: Mean positive and negative aging perception scores were 31.45 (SD = 4.18) and 18.23 (SD = 4.45), respectively. The average HLQ-QA score was 47.84 (SD = 6.59), with competency scores ranked as: appraising (M (mean) = 12.12, SD = 1.73), understanding (M = 12.03, SD = 1.91), accessing (M = 11.90, SD = 1.84), and applying (M = 11.80, SD = 2.04). Regression analyses showed that positive perceptions significantly improved health literacy (β = 0.197, p = 0.013), while negative perceptions reduced it (β = −0.227, p = 0.005). Conclusions: Positive attitudes toward aging enhance older men’s health literacy, whereas negative perceptions hinder their ability to process health information. Community programs should focus on men with lower education levels, those living alone, and those without Internet access. Promoting positive attitudes and combating ageism are critical for improving health literacy and achieving healthy aging.